Highly filled thermoplastic elastomers from ground tire rubber, maleated polyethylene and high density polyethylene. (April 2013) - Kakroodi, A R; Rodrigue, D
Abstract : In this work, maleated polyethylene (MAPE) is proposed as a matrix to produce thermoplastic elastomers based on ground tire rubber (GTR) with a focus on high GTR contents (50–90 wt-%). The compounds were also compared with thermoplastic elastomers based on high density polyethylene (HDPE) as the matrix. Scanning electron microscopy images revealed high compatibility and very good interfacial adhesion between the MAPE matrix and rubber particles. Samples in the range of 50–70% of GTR in MAPE showed very good tensile elongation at break and tensile strength, while the properties decreased for samples at higher GTR content. The elasticity of the thermoplastic elastomers was also investigated via compression set measurements. All GTR/MAPE compounds showed highly elastic behaviour with elasticity increasing with GTR content. Tensile and elastic recovery values of HDPE/GTR compounds, with and without MAPE coupling agent, were significantly lower than those based on MAPE. High stability was observed for both MAPE and HDPE based compounds after thermal aging at 70°C. Thermal degradation was also characterised with respect to changes in melt viscosities.